Drug therapy problem in the pharmacotherapeutic follow-up of patients with tuberculosis, HIV/AIDS and in co-infection: integrative review (Research, Society and Development, 2022)
Pharmaceutical care is the responsible provision of pharmacotherapy and aims to achieve defined outcomes that improve quality of life. Tuberculosis, HIV/AIDS and co-infected patients use a large amount of medication, which increases the risk of having drug therapy problems. The objective of this study was to verify the evidence available in the literature on drug therapy problems in the pharmacotherapeutic follow-up of patients receiving treatment for tuberculosis, HIV/AIDS and in co-infection. This is an integrative literature review study, searching for articles in the latin american literature in science and Health and PubMed databases. Eighteen articles related to the topic were selected. Regarding the methodology, eight used the Dader method, seven the pharmacist’s workup of drug therapy and three used other methods of classification of drug therapy problems. Positive results were found when pharmaceutical guidance was applied to patient care, identifying a lower occurrence of drug therapy problem when there was an intervention of the pharmacist with the clinical team. It was observed that most drug therapy problem reported were related to drug safety, followed by indication. These studies reinforce the idea that pharmaceutical intervention can reduce the number of drug therapy problem and increase the quality patients’ care.